The Drosophila transcription factor tramtrack (TTK) interacts with Trithorax-like (GAGA) and represses GAGA-mediated activation. - Pagans, S.; Ortiz-Lombardia, M.; Espinas, M.L.; Bernues, J.; Azorin, F. (Nucleic Acids Research, 2002)
In this study, we report the interaction of the Drosophila transcription factors Trithorax-like (GAGA) and tramtrack (TTK). This interaction is documented both in vitro, through GST pull-down assays, as well as in vivo, in yeast and Schneider S2 cells. GAGA and TTK share in common the presence of an N-terminal POZ/BTB domain that was found to be necessary and sufficient for GAGA-TTK interaction. Structural models that could account for this interaction are discussed. GAGA is known to activate the expression of many genes in Drosophila. On the other hand, TTK was proposed to act as a maternally provided repressor of several pair-rule genes, such as even-skipped (eve). As with many Drosophila genes, eve contains at its promoter region binding sites for GAGA and TTK. Here, in transient expression experiments, we showed that GAGA activates transcription from the eve stripe 2 promoter element and that TTK inhibits this GAGA-dependent activation. Repression by TTK of the eve promoter requires its activation by GAGA and depends on the presence of the POZ/BTB domains of TTK and GAGA. These results indicate that GAGA-TTK interaction contributes to the regulation of gene expression in Drosophila.